INNOVATIVE SIGNIFICANCE OF INDICATORS OF PARTIAL RENAL FUNCTIONS IN CHRONIC TUBULOINTERSTITIAL NEPHRITIS IN CHILDREN - Akhmedzhanov I.A.; Akhmedzhanova N.I.; Izomiddinova M.K. (PEDAGOGS, 2024)
Annotation. Despite the progress achieved in the diagnosis and treatment of nephropathies, in almost 25% of patients this pathology continues to progress, which leads to a deterioration in the quality of life of patients.